Analysis of Product Marketing Strategy: Combined SWOT and QSPM Approach - Andriyanto, Dicky; Kurniawati, Dewi; Wiguna, Ardhitya Alam; Mayasari, Financia; Resya, Fachmi; Universitasari, Pascawati Savitri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Situbondo Regency is dominated by farmers, providing residents with opportunities to become entrepreneurs in rice production. The rice business in Situbondo Regency needs to be developed to overcome the challenge of finding appropriate strategies for local conditions, to maintain more stable economic growth. This study has several objectives: to analyse strengths, weaknesses, opportunities, and threats using the IFE, EFE, and IE matrices; and to formulate and determine accurate key strategies for use by rice businesses in Situbondo Regency through the SWOT matrix and QSPM. Eight alternative strategies were identified from the SWOT and in-depth market evaluation (TAS = 7.81) using the QSPM as the primary framework for the strategies used by rice entrepreneurs in Situbondo Regency. Empirical findings show that the main internal strength in the form of financial records has been well implemented, while the main weakness is that marketing has not been evenly distributed. On the other hand, external factors indicate that the main business opportunities are the absence of price differences among competitors, computerised customer data collection, many farmers growing rice around the business location, and interest in organic rice.